2000
DOI: 10.1056/nejm200006083422302
|View full text |Cite
|
Sign up to set email alerts
|

The Causes and Risk of Stroke in Patients with Asymptomatic Internal-Carotid-Artery Stenosis

Abstract: The risk of stroke among patients with asymptomatic carotid-artery stenosis is relatively low. Forty-five percent of strokes in patients with asymptomatic stenosis of 60 to 99 percent are attributable to lacunes or cardioembolism. These observations have implications for the use of endarterectomy in asymptomatic patients. Without analysis of the risk of stroke according to cause, the absolute benefit associated with endarterectomy may be overestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
367
0
23

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 639 publications
(401 citation statements)
references
References 40 publications
6
367
0
23
Order By: Relevance
“…In fact, data from NASCET trial showed that carotid endarterectomy is more beneficial in patients with intracranial stenosis. 18 Similarly, lacunar strokes were included as endpoint as they had been associated with a poor hemodynamic response in patients with carotid stenosis. 11 Another point to discuss is the relatively high incidence of stroke in our cohort compared with more recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, data from NASCET trial showed that carotid endarterectomy is more beneficial in patients with intracranial stenosis. 18 Similarly, lacunar strokes were included as endpoint as they had been associated with a poor hemodynamic response in patients with carotid stenosis. 11 Another point to discuss is the relatively high incidence of stroke in our cohort compared with more recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…For those with 75% to 94% stenosis, the rates were 27.1% and 18.5%, respectively ( Figure 2). 17 Because NASCET enrolled symptomatic patients, however, understanding the implications of stroke rate on the side of an asymptomatic stenosis opposite a symptomatic stenosis is problematic. 17 The Asymptomatic Carotid Atherosclerosis Study (ACAS) 18 enrolled asymptomatic patients with stenosis Ն60%; even without surgery, absolute stroke rates were low: 5.0% at 2 years with a 1.2% absolute risk reduction by carotid endarterectomy (to 3.8%) by the most highly skilled surgeons available.…”
Section: Cerebrovascular Atherosclerotic Diseasementioning
confidence: 99%
“…The IPH was defined as hyperintense compared to adjacent muscle (signal intensity ratio ≥1.5:1) on SNAP imaging 13. The luminal stenosis was measured using WASID14 criteria for intracranial arteries and NASCET15 criteria for extracranial carotid arteries on SNAP angiography. The presence or absence and the lesion volume of acute ischemic lesions (AIL) on DWI images were evaluated.…”
Section: Methodsmentioning
confidence: 99%